Variable carbon catabolism among salmonella enterica serovar typhi isolates - Chai, L.C.; Kong, B.H.; Elemfareji, O.I.; Thong, Kwai Lin (Public Library of Science, 2012)
BACKGROUND: Salmonella enterica serovar Typhi (S. Typhi) is strictly a human intracellular pathogen. It causes acute systemic (typhoid fever) and chronic infections that result in long-term asymptomatic human carriage. S. Typhi displays diverse disease manifestations in human infection and exhibits high clonality. The principal factors underlying the unique lifestyle of S. Typhi in its human host during acute and chronic infections remain largely unknown and are therefore the main objective of this study. METHODOLOGY/PRINCIPAL FINDINGS: To obtain insight into the intracellular lifestyle of S. Typhi, a high-throughput phenotypic microarray was employed to characterise the catabolic capacity of 190 carbon sources in S. Typhi strains. The success of this study lies in the carefully selected library of S. Typhi strains, including strains from two geographically distinct areas oftyphoid endemicity, an asymptomatic human carrier, clinical stools and blood samples and sewage-contaminated rivers. An extremely low carbon catabolic capacity (27% of 190 carbon substrates) was observed among the strains. The carbon catabolic profiles appeared to suggest that S. Typhi strains survived well on carbon subtrates that are found abundantly in the human body but not in others. The strains could not utilise plant-associated carbon substrates. In addition, α-glycerolphosphate, glycerol, L-serine, pyruvate and lactate served as better carbon sources to monosaccharides in the S. Typhi strains tested. CONCLUSION: The carbon catabolic profiles suggest that S. Typhi could survive and persist well in the nutrient depleted metabolic niches in the human host but not in the environment outside of the host. These findings serve as caveats for future studies to understand how carbon catabolism relates to the pathogenesis and transmission of this pathogen.